Analisis Pengaruh Ekspor dan Impor Terhadap Pertumbuhan Ekonomi di Indonesia - Jumawan, Jumawan; Prasetyo, Andhika Rifki (Prisani Cendekia, 2024)
This study aims to analyze the impact of exports and imports on Indonesia's economic growth over the period from 1999 to 2020. The method used in this study is the Error Correction Model (ECM) to evaluate both short-term and long-term relationships between these variables. The data utilized in this research are sourced from the Central Bureau of Statistics (BPS) and the World Bank, encompassing the values of exports, imports, and Indonesia's Gross Domestic Product (GDP). The results show that exports have a positive and significant impact on economic growth in the long term, while imports have a negative and significant impact. In the short term, exports also show a significant positive influence, whereas imports have a significantly negative effect on economic growth. These findings underscore the importance of maintaining a balance between exports and imports to ensure sustainable economic growth. Based on the results of the study, the suggested policy implications include increasing access to international markets, better management of imports, economic diversification, and strengthening logistical infrastructure.